Harmonisasi Kasih Karunia dan Taurat: Relevansi Teologis dalam Kehidupan Kristen Kontemporer - Jusup Maria Setiawan Sutandar; Hikman Sirait; Esti Rahayu (Phronesis: Jurnal Teologi dan Misi, 2025)
This study examines the theological discourse surrounding grace and the Torah, a subject that has generated considerable debate among contemporary Christian communities. A prevalent view asserts that the grace made available through the death of Jesus Christ renders the Torah obsolete, thereby releasing Christians from its observance. In contrast, another perspective upholds the continued relevance of the Torah, particularly the Ten Commandments, as a moral and spiritual foundation. This ongoing debate underscores the need for a more nuanced understanding of the relationship between grace and the Torah in the context of Christian life today. Accordingly, the objective of this research is to investigate the potential harmonisation between grace and the Torah within contemporary Christian practice. Employing a descriptive qualitative approach, this study utilises a literature review method, drawing primarily on biblical texts and supplemented by relevant peer-reviewed scholarly sources. The findings suggest that grace and the Torah need not be viewed in opposition, but rather as complementary aspects of Christian ethics and spirituality. From both philosophical and moral perspectives, the study affirms that Christians—whether they emphasise divine grace or Torah observance—are equally called to embody a life of moral integrity and ethical responsibility.